2008
DOI: 10.2174/156800908783769391
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cell Death in Tumors by Activating Caspases

Abstract: Cytotoxic approaches to killing tumor cells, such as chemotherapeutic agents, γ-irradiation, suicide genes or immunotherapy, have been shown to induce cell death through apoptosis. The intrinsic apoptotic pathway is activated following treatment with cytotoxic drugs, and these reactions ultimately lead to the activation of caspases, which promote cell death in tumor cells. In addition, activation of the extrinsic apoptotic pathway with death-inducing ligands leads to an increased sensitivity of tumor cells tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 104 publications
0
38
0
Order By: Relevance
“…Most drug compounds reportedly induce apoptosis through intrinsic death signaling pathways. Caspase-3 is regarded as a member of the apoptosis executioner caspases and cleaves many key proteins in apoptosis [40]. We found that CXCR4 knockdown can increase the activation of caspase-3 and induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most drug compounds reportedly induce apoptosis through intrinsic death signaling pathways. Caspase-3 is regarded as a member of the apoptosis executioner caspases and cleaves many key proteins in apoptosis [40]. We found that CXCR4 knockdown can increase the activation of caspase-3 and induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that activated caspases are the critical components of the execution phase of cell death in most forms of apoptosis. Therefore, factors affecting caspase activation might be important determinants of drug sensitivity [21]. We found that cell death was prevented by the pancaspase inhibitor Z-VAD, suggesting that MMPT induces caspase-dependent apoptosis in H1792 cells.…”
Section: Discussionmentioning
confidence: 87%
“…In vitro studies also demonstrated that large numbers of BCL1 cells suppress the growth of CD8 + T cells in a contact-dependent manner. Since BCL1 tumor cells express Fas-Ligand, binding to Fas on target cells likely initiates caspase-mediated apoptosis [35]. Our co-culture assays showed that high ratios of BCL1 tumor cells were needed to induce caspase-3 activation in CD8 + T cells suggesting that prolonged or repeated contact between BCL1 tumor cells and cytotoxic T cells might be required to kill the latter.…”
Section: Discussionmentioning
confidence: 93%
“…Caspase-3 is a member of the family of effector caspases and its active form triggers the apoptosis pathway. Caspase-3 activation can be initiated in target cells by the binding of Fas-ligand (FasL) to its surface receptor, CD95 (Fas), which leads to subsequent activation of the caspase-3-mediated apoptosis [35]. Since BCL1 tumor cells express FasL (data not shown), we questioned whether tumor cell-mediated inhibition of CD8 + T cells was induced via the FasL-mediated caspase cascade.…”
Section: Resultsmentioning
confidence: 99%